Characterization of Three Novel IMP Metallo-β-Lactamases, IMP-89, IMP-91, and IMP-96, and Diverse blaIMP-Carrying Accessory Genetic Elements from Chinese Clinical Isolates - Xinyue Li; Xiaofei Mu; Fangzhou Chen; Xiuhui Lu; Jiaqi He; Yali Zheng; Dongsheng Zhou; Zhe Yin; Peng Wang (Microbiology Spectrum, 2023)
ABSTRACT Three novel imipenemase (IMP)-type metallo-β-lactamases (MBLs), referred to as IMP-89, IMP-91, and IMP-96, were detected in three clinical isolates from China. Antimicrobial susceptibility tests indicated these novel enzymes were resistant to most β-lactams, and IMP-96 with a Ser262Gly mutation had higher activity against meropenem than its point mutant. We then collected sequence data on all 91 available IMP variants for phylogenetic analysis. To further analyze the genetic environment of blaIMP, an extensive comparison was applied to nine accessory genetic elements (AGEs), including six sequenced blaIMP-carrying AGEs in this study and three others from GenBank. These nine AGEs were divided into three groups: three IncpJBCL41 plasmids, Tn6417 and its two derivatives, and three Tn6879-related integrative and conjugative elements (ICEs). All blaIMP genes in this study were captured by class 1 integrons. In the integrons, blaIMP genes usually coexisted with other resistance genes, which further impeded clinical antibacterial treatment. The emergence of new IMP variants and the diversity and complexity of their genetic environment make the prevention and control of drug-resistant strains critical, requiring serious attention from clinical and public health management departments. IMPORTANCE The spread of IMP-type MBLs has increased dramatically in recent years. We discovered three novel IMP variants from three clinical isolates in China. We summarized the classification and evolutionary relationship of all available IMP variants. Moreover, we detailed the genetic characteristics of blaIMP-carrying accessory genetic elements in five clinical isolates. Given the risk of rapid and extensive spread of blaIMP genes, we suggest that continuous surveillance is crucial to combat the acquisition and transmission of blaIMP genes by bacteria, which can impede clinical therapy effectiveness.